PENGARUH LESSON STUDY TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS IV DI SDN KAIBON 03 - Chusma Candra Winedar; Endang Sri Maruti; Katmini (STKIP Subang, 2024)
CHUSMA CANDRA WINEDAR: The influence of Lesson Study on the Cognitive Student Learning of Grade IV Student of SDN Kaibon 03. PTK. Madiun: Teacher Professional Education Study Program, PGRI University of Madiun, 2024. This research is motivated by the quality of teachers who are still old products with a teaching system that only focuses on input, process and output aspects while outcomes are not considered. Given the importance of measuring and assessing students, educators should have knowledge of the basic concepts of assessment and the skills to apply them in educational activities because so far most educators have carried out assessments more referring to cognitive aspects. Teacher quality can determine how learning will take place and how learning objectives can be achieved. The purpose of this study was to determine the effect of learning using Lesson Study on the cognitive learning outcomes of fourth grade students of SDN Kaibon 03. This study is a classroom action research with a population covering all students of SDN Kaibon 03 consisting of six classes. Of the six classes, class IV was randomly selected as a sample. Class IV as a control class that was given conventional learning model treatment first and then became an experimental class that was given Lesson Study treatment. The data collection technique in this study was a test while the instrument used to collect data included students' cognitive learning outcome test questions. For data analysis techniques, the t-test was used. The results of the study at a significance level of 0.05 showed that the cognitive learning outcomes of students whose learning uses Lesson Study are better than those whose learning uses conventional models.